PENGARUH PENDEKATAN KONTEKSTUAL DENGAN MEDIA KERTAS LIPAT TERHADAP HASIL BELAJAR OPERASI HITUNG PECAHAN - Ariyandhini, Fatimah Ariyandhini; Hermahayu, Hermahayu; Mahardika, Astuti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
The purpose of this study is to know the effect of contextual approach with fold paper media to learning product at the fourthgrade students of SD Negeri Kleteran 3 Grabag. This study use true experimental design with pretest-posttest control groupdesign using control group and experiment group. The population of this study are all of fourth grade students of SD NegeriKleteran 3 and SD Negeri Grabag 3. Sampling technique used is total sampling. Samples of this study are 64 students.Methods of data collection using learning product test and observation. The effect of contextual approach with fold paper mediato students learning product is analyzed by Independent Sample t-test method using program of SPSS 16.0 for Windows.Based on the analysis result, the value of calculate t is 3.335 and the value of table t is 1.999 (calculate t > table t) and thevalue of significant 2-tailed is 0.001 (<0.05) that means there is a significant difference between the posttest result of controlgroup and the posttest result of experiment group. So, it means that contextual approach with fold paper media has affect tolearning product of student.